B cells from Patients with Rheumatoid Arthritis Show Conserved CD39-Mediated Regulatory Function and increased CD39 Expression After Positive Response to Therapy. Issue 1 (8th January 2021) - Zacca, E.R.; Amezcua Vesely, M.C.; Ferrero, P.V.; Acosta, C.D.V.; Ponce, N.E.; Bossio, S.N.; Mussano, E.; Onetti, L.; Cadile, I.; Acosta Rodríguez, E.V.; Montes, C.L.; Gruppi, A.
Graphical abstract: Highlights: When compared cross-sectionally, RA patients under different treatments do not differ from each other or from HD in terms of the frequency of B cell subsets expressing CD39 and/or CD73. The capacity of B cells to regulate the proliferation and TNF-production of CD4 + T cells mediated by CD39 is not affected in patients with RA. In a longitudinal analysis, RA patients with good response to therapy exhibited an increase in CD39 expression on B cells after treatment while most of the non-responders exhibited a reduction in CD39 expression. B cells from some good responders increased their CD39 expression after treatment, which correlated with less DAS28, rheumatoid factor and anti-cyclic citrullinated peptide antibodies. Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by progressive joint destruction associated with increased pro-inflammatory mediators. In inflammatory microenvironments, exogenous ATP (eATP) is hydrolyzed to adenosine, which exerts immunosuppressive effects, by the consecutive action of the ectonucleotidases CD39 and CD73. Mature B cells constitutively express both ectonucleotidases, converting these cells to potential suppressors. Here, we assessed CD39 and CD73 expression on B cells from treated or untreated patients with RA. Neither the frequency of CD73 + CD39 + and CD73 - CD39 + B cell subsets nor the levels of CD73 and CD39 expression on B cells from untreated or treated RA patients showed significant changes in comparison to healthy controls (HC). CpG+IL-2-stimulated B cells from HC or untreated RA patients increased their CD39 expression, and suppressed CD4 + and CD8 + T cell proliferation and intracellular TNF-production. A CD39 inhibitor significantly restored proliferation and TNF-producing capacity in CD4 + T cells, but not in CD8 + T cells, from HC and untreated RA patients, indicating that B cells from untreated RA patients conserved CD39-mediated regulatory function. Good responder patients to therapy (R-RA) exhibited an increased CD39 but not CD73 expression on B cells after treatment, while most of the non-responder (NR) patients showed a reduction in ectoenzyme expression. The positive changes of CD39 expression on B cells exhibited a negative correlation with disease activity and rheumatoid factor levels. Our results suggest modulating the ectoenzymes/ADO pathway as a potential therapy target for improving the course of RA.